The announcement effect : the impact of early warnings of future thresholds under different framing and risk contexts - Child, Alexander Fairfax (Department of Social Development, 2015)
The effect of announcing future institutional change is investigated in three different contexts: a gains frame, a loss frame, and a loss frame with risk. The institutional change is the transition from a normal public goods game into a threshold public goods game. Announcements may change subject behaviour, through influencing their expectations, before the implementation of the new institution (adjustment effect) and/or after the implementation (adaptation effect).We find that announcements in the gains frame cause zero adjustment effects and negative adaptation effects; while announcements in the loss frame cause positive adjustment and adaptation effects. However, including risk into the threshold phase of the loss frame causes the announcements to have zero effects. These results have important implications for the climate change debate.